2021
DOI: 10.1101/2021.12.15.21267774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delivering HIV pre-exposure prophylaxis (PrEP) care online: A scoping review

Abstract: ObjectivesHIV pre-exposure prophylaxis (PrEP), in which people take HIV medication to prevent HIV acquisition, is a highly effective method of HIV prevention; however, global implementation of PrEP is patchy. PrEP provision will need to be upscaled significantly to achieve UNAIDS/WHO goals of elimination of HIV transmission. Online provision of PrEP care could enhance access to, and delivery of, care at scale. We explored the extent to which PrEP care has been delivered online to inform the development of a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…1) information delivered online on websites (e.g., World Health Organisation [WHO], 2022; Magee et al, 2012) or through online education programmes (e.g., Mustanski et al, 2015;Lacombe-Duncan et al, 2021); 2) advice and support online which may involve use of telecommunication such as video calls, live chats, email, or text services with charity or community-based organisation staff or peers (e.g., Radix et al, 2022;Skeen & Cain, 2022); and 3) clinical care provided online, such as STI/HIV self-sampling kits and test results (e.g., Bauermeister et al, 2015;Estcourt et al, 2017;Hottes et al, 2012;Ling et al, 2010;Brugha et al, 2011);PrEP (ePrEP;Kincaid et al, 2021); partner notification (PN) and testing options (e.g., Golden et al, 2022;Flowers et al, 2021;Mimiaga et al, 2008); and consultations (eConsult) and telemedicine (e.g., Sequeira et al, 2021;Lucas et al, 2023).…”
Section: A Potential Solutionmentioning
confidence: 99%
“…1) information delivered online on websites (e.g., World Health Organisation [WHO], 2022; Magee et al, 2012) or through online education programmes (e.g., Mustanski et al, 2015;Lacombe-Duncan et al, 2021); 2) advice and support online which may involve use of telecommunication such as video calls, live chats, email, or text services with charity or community-based organisation staff or peers (e.g., Radix et al, 2022;Skeen & Cain, 2022); and 3) clinical care provided online, such as STI/HIV self-sampling kits and test results (e.g., Bauermeister et al, 2015;Estcourt et al, 2017;Hottes et al, 2012;Ling et al, 2010;Brugha et al, 2011);PrEP (ePrEP;Kincaid et al, 2021); partner notification (PN) and testing options (e.g., Golden et al, 2022;Flowers et al, 2021;Mimiaga et al, 2008); and consultations (eConsult) and telemedicine (e.g., Sequeira et al, 2021;Lucas et al, 2023).…”
Section: A Potential Solutionmentioning
confidence: 99%
“…Such healthcare includes online postal self-sampling (OPSS) for sexually transmitted infection (STI) and blood borne virus (BBV) testing (e.g., [5][6][7][8]. More complex online clinical care pathways are also in development, such as the eSexual Health Clinic for accessing STI test results and treatment (9) and ePrEP for accessing HIV prevention medication, pre-exposure prophylaxis (PrEP) (10). For many people, the initial steps to accessing sexual healthcare, both online and traditional (i.e., in-person/phone), are seeking sexual health information and support online (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Digital services are already integral parts of care pathways for people accessing pre-exposure prophylaxis (PrEP) in many parts of the UK and considerable research is underway 1. Many services offered some elements of PrEP care online before 2020, which enabled rapid transition to hybrid online and telephone based PrEP care during the pandemic 23. Research presented at a recent national conference showed the acceptability of online PrEP 456…”
mentioning
confidence: 99%